Antifatigue and microbiome reshaping effects of yak bone collagen peptides on Balb/c mice. (April 2023) - Feng, Ruifang; Zou, Xiaoxiao; Wang, Kai; Liu, Huaigao; Hong, Hui; Luo, Yongkang; Tan, Yuqing
Abstract: As the main by-product of yak ( Bos grunniens ) processing, yak bone was discarded or simply processed for low-value production. The development of yak bone collagen peptides (YBP) has shown great potential. In the study, the 1 g/kg· BW peptides were supplied (the group of YBP) or not supplie the control group) in the Balb/c mice diet for 18 weeks. Peptide supplementation prolonged the swimming time of mice by 25% and 37% for twice tests, respectively, accompanied by the increased content of glucose (Glu), lactate dehydrogenase (LDH), superoxide dismutase (SOD), glutathione (GSH), and decreased content of lactic acid (LA), blood ammonia (BA) in blood. YBP intervention promoted the relative abundance of Bacteroides, Blautia, Muribaculum, etc. The proportion of amino acid and carbohydrate transport and metabolism increased among all the predicted functions from the orthologous groups of proteins (COG) database. Besides that, after YBP intervention, many up-regulated proteins in the liver were involved in the protein and carbohydrate metabolism-related pathways, and the proteins in lipid metabolism-related pathways were down-regulated. This study firstly clarified the antifatigue and gut microbiome reshaping effects of YBP on Balb/c mice and provided the theoretical basis for future development. Graphical abstract: Image 1 Highlights: The YBP's antifatigue capacity is discovered for the first time. The potent antioxidant capacity of YBP in vivo was observed. YBP intervention reshaped the gut microbiome. YBP intervention increased protein and carbohydrate metabolism.